Training of Health Protocol Agents at SMK Ma'arif NU Banjarsari to Prepare Face-To-Face Learning in the New Normal Era (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
In 2021, the Ministry of Education and Culture had allowed face-to-face learning (PTM) in schools with various terms and conditions, including the zone and level of PPKM (Enforcement of Community Activity Restrictions) in the area. Some parents very well welcome this policy, but others are still hesitant to allow their children to join PTM. Observing this, school readiness in maintaining the implementation of the Health Protocol is the primary key to success in the new normal era. One of the efforts is to establish a health protocol agency consisting of teachers and student representatives. Health protocol agents are tasked with ensuring the implementation of health protocols in schools from the arrival to the return of all school residents.